First feeding of diploid and triploid yellowtail tetra Astyanax altiparanae: An initial stage for application in laboratory studies - Bertolini, Rafaela Manchin; Senhorini, Jose Augusto; Nascimento, Nivaldo Ferreira do [UNESP]; Pereira-Santos, Matheus [UNESP]; Okada Nakaghi, Laura Satiko [UNESP]; Moreira Peres, Wellington Adriano; Silva, Regiane Cristina da [UNESP]; Yasui, George Shigueki (Wiley-Blackwell, 2018)
In this study, the aim was to establish a protocol for first feeding of diploid and triploid yellowtail tetra Astyanax altiparanae in laboratory conditions. The fry were fed with five different diets: (i) Artemia franciscana nauplii, (ii) plankton, (iii) dry food, (iv) Artemia franciscana nauplii+plankton, and (v) Artemia nauplii+plankton+dry food. Additionally, the growth and survival rates of diploid and triploid individuals were also evaluated. On day 10, the length of the fish between the treatments differed significantly (p=.0001) and ranged from 4.07 +/- 0.06mm (dry food) to 8.50 +/- 0.64mm (plankton+Artemia). The sizes of the fish increased with time, except for the fish fed with dry food. The survival rates were similar for the fish fed with the four diets and ranged from 80.7 +/- 5.4% (dry food+plankton+Artemia to 92.0 +/- 1.6% (plankton+Artemia), but differed from the fish fed with dry food (17.7 +/- 5.8%, p=.0017). Diploids and triploids did not present differences on day 0 (p=.2252) and on day 10 (p=.4844) when the fish presented 6.77 +/- 0.25mm and 6.54 +/- 0.15mm respectively. Survival of diploids (87.3 +/- 5.13%) and triploids (74.67 +/- 2.30%) were also similar (p=.0285). These data are innovative and useful for establishing protocols for this species in both academic and applied sciences.
Keywords: characin; chromosome; feeding; fish; larviculture; polyploid